2015
DOI: 10.1016/j.juro.2014.10.124
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pain in Autosomal Dominant Polycystic Kidney Disease and Anatomy of Renal Innervation

Abstract: Purpose: Chronic pain is a prominent feature of autosomal dominant polycystic kidney disease (ADPKD) that is difficult to treat and manage, often resulting in a decrease in quality of life. Understanding the underlying anatomy of renal innervation and different etiologies of pain that occur in ADPKD can help to guide proper treatments to manage pain. Reviewing the previously studied treatments for pain in ADPKD can help to characterize treatment in a stepwise fashion. Materials and Methods: We performed a lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 49 publications
(67 reference statements)
0
24
0
Order By: Relevance
“…The majority of these fibers converge around the ventral surface of the renal artery. 1 Histologic studies have confirmed these nerves traverse along the adventitia and periadventitial fat allowing for surgical disruption along the renal hilum. Studies have implied that renal innervation also arise from outside the hilum due to the aorticorenal and intermesentric ganglia connections that must be addressed during denervation techniques.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The majority of these fibers converge around the ventral surface of the renal artery. 1 Histologic studies have confirmed these nerves traverse along the adventitia and periadventitial fat allowing for surgical disruption along the renal hilum. Studies have implied that renal innervation also arise from outside the hilum due to the aorticorenal and intermesentric ganglia connections that must be addressed during denervation techniques.…”
Section: Discussionmentioning
confidence: 88%
“… 5 Animal and cadaveric studies have detailed the complex neural innervation pathway of the kidney. 1 , 5 This network of ganglia and neural filaments course with vascular structures of the renal hilum. The majority of these fibers converge around the ventral surface of the renal artery.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Chronic pain is usually attributable to cyst enlargement that causes kidney capsule stretching or to marked enlargement of the kidneys and/or liver that causes musculoskeletal back pain. Managing chronic pain can be challenging and requires a multidisciplinary stepwise approach with multiple strategies, including physical therapy interventions, pain medications, cyst sclerosis and laparoscopic cyst fenestrations and renal denervation procedures [208][209][210] .…”
Section: Management Adpkdmentioning
confidence: 99%